The Photosynthetic Unit in Chlorella Measured by Repetitive Short Flashes - Myers, Jack (1971)
Apparent size of the photosynthetic unit in Chlorella pyrenoidosa was estimated by the method of Emerson and Arnold: rate of oxygen evolution was measured under repetitive saturating flashes of about 10-microsecond duration separated by dark periods of 0.033 to 0.100 second. Cells used were taken from six steady state cultures maintained at different light intensities. Cell characteristics included a variation in chlorophyll content from 1 to 5%. Apparent size of the photosynthetic unit varied systematically with chlorophyll content in the range of 1560 to 2350 chlorophylls per O(2) per flash. Values for unit size showed no unusual statistical distribution and were not changed significantly by addition of low level background light at 645 or 705 nanometers. Maximal rate of unit turnover, calculated from light-saturated rate and unit size, varied inversely with chlorophyll content in the range of 70 to 180 per second.